Pengaruh Struktur Modal, Struktur Kepemilikan, Faktor Teknikal Terhadap Profitabilitas dengan Total Pendapatan Sebagai Variabel Moderasi Pada Sub Sektor Perkebunan Di Bursa Efek Indonesia Periode 2015-2018 - Yunan Surono; Amilia Paramita S; Ali Akbar (J-MAS (Jurnal Manajemen dan Sains), 2020)
This research aims to look at the influence of capital structure, ownership structure, technical factors on profitability with total income as a moderation variable in the plantation sub-sector on the Indonesia Stock Exchange period 2014 – 2018. This research, using secondary data, is data obtained from official reports issued by issuers, institutions and competent authorities. This study used Smart PLS 3.0 where all latent variables in this study had reflective indicators. The results showed that 1). capital structure has no effect on profitability, and has a negative (debilitating) direction. 2). The ownership structure has no effect on profitability, but has a positive direction (strengthening). 3). Technical factors have no effect on profitability, but have a positive direction (strengthening) 4). Moderation variables i.e. total income are not able to moderate the relationship between capital structure variables to profitability variables, with positive direction (strengthening). 5). Total revenue variables are unable to moderate the relationship between ownership structure variables to profitability variables in a positive (corroborating) direction. 6). Total revenue variables are unable to moderate the relationship between technical factor variables to profitability variables in a positive (strengthening) direction.